Reading Nablus’ urban print: Towards an understanding of its morphology - Taher, Muath (2018)
Nablus old center stands as a typical Arab city with a relevant geographical location. Successive historical periods distinguish its history - from Canaanite to Roman, Byzantine, Islamic, Crusader or Ottoman - till nowadays. This cultural diversity has layered chronological strata on its urban fabric. Therefo re, diverse historical characteristics reflected in the city’s urban morphology have undergone continued physical and functional transformations, not only gradually by time and various socio - cultural, economic or political factors, but also radically by ea rthquakes and war destructions. Present - day Nablus’ physical image echoes a palimpsest of urban/social identities and an asset for a ve ry sensitive collective memory. This paper examines the formation, evolution and constitution of the old city of Nablus b y a retrospective analysis that searches the morphological momentum for each phase in articulation with a reflection around its historical meaning for the city. Methodologically, this study is conducted on both urban and architectural levels, surveying str eet hierarchy and plot distribution. This understanding will be extremely important for an accurate perception of this tissue in order to advocate for a concerned idea of the city’s reconstruction, following recent urban annihilations. At a time when urban rehabilitation pushes plans for quick and immediate results, reading Nablus’ urban morphology can work as the lacking tool for an instructed and operative regeneration.